The Evaluation of the Performance of MSMEs Leaders in Mandailing Natal Regency - Faliza, Nur (Jurnal Informatika Ekonomi Bisnis, 2023)
This study examines the relationship between servant leadership, innovativeness, competence, and leadership performance in Micro, Small, and Medium Enterprises (MSMEs) in Mandailing Natal regency. The research aims to determine the significance of these variables and their impact on MSMEs' leadership effectiveness. The study employed a hypothesis testing approach, using a significance level of 0.05, to analyze the collected data. The results revealed that servant leadership, as indicated by a p-value of 0.007, innovativeness (p-value of 0.000), and competence (p-value of 0.000) significantly influenced the performance of MSMEs leaders. The findings suggest that leaders who prioritize serving others, demonstrate innovative thinking, and possess the necessary competencies are associated with improved performance in MSMEs leadership roles. The discussion highlights the importance of adopting a service-oriented leadership style, fostering innovation, and investing in leadership competencies to enhance leadership effectiveness in MSMEs. These results have practical implications for MSMEs in Mandailing Natal regency. By embracing servant leadership values, fostering a culture of innovation, and developing leadership competencies, MSMEs can improve their overall performance, operational efficiency, and strategic decision-making. It is important to note that these findings are specific to the context of MSMEs in Mandailing Natal regency. Further research in different settings and industries would contribute to a broader understanding of the relationship between these variables.